KOMPETENSI LINGKUNGAN KERJA FISIK DAN KINERJA PEGAWAI - Hidayat, Muhammad (Jurnal Ilmu Administrasi Negara, 2016)
Competence, Physical Work Environment and Performance. This study aims to determine the effect of competence and physical work environment on the performance of the Civil Service at the Library and Archives of Pekanbaru type of research is quantitative descriptive statistical test and multiple linear regression analysis method. The sample used includes all Civil Servants in the neighborhood of Library and Archives Pekanbaru City that is numbered 30 people.The results showed that the competence and lingkkungan physical labor each have positive and significant impact on the performance of the Civil Service at the Library and Archives of Pekanbaru. The effect of competence and physical work environment together influence the performance of 84,9%.